2021
DOI: 10.3832/ifor3626-014
|View full text |Cite
|
Sign up to set email alerts
|

Mid-rotation fertilization and liming of Pinus taeda: growth, litter, fine root mass, and elemental composition

Abstract: Biogeosciences and Forestry Biogeosciences and ForestryMid-rotation fertilization and liming of Pinus taeda: growth, litter, fine root mass, and elemental composition William Magrim Adam (1) , Valdécio Dos Santos Rodrigues (2) , Ederlan Magri (2) , Antônio Carlos Motta Vargas (2) , Stephen A Prior (3) , Leandro Moraes Zambon (4) , Rubia Luciane Dominschek Lima (2)Forest floor litter can influence biogeochemical cycling and root growth in Pinus taeda systems, especially on low soil fertility sites. The impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…A significant increase in wood production of loblolly pine in response to fertilization, as revealed in the present study and supported by findings of multiple studies (Fox et al 2007, Carlson et al 2014, Adam et al 2021, Pereira et al 2022, occurs due to a series of effects related to the improvement of plant nutrition and belowground and aboveground growth. Fertilization favored enhanced root growth probably due to improved nutritional status (Alvarez-Clare & Mack 2015, Consalter et al 2021a.…”
Section: General Effect Of Fertilizationsupporting
confidence: 89%
See 3 more Smart Citations
“…A significant increase in wood production of loblolly pine in response to fertilization, as revealed in the present study and supported by findings of multiple studies (Fox et al 2007, Carlson et al 2014, Adam et al 2021, Pereira et al 2022, occurs due to a series of effects related to the improvement of plant nutrition and belowground and aboveground growth. Fertilization favored enhanced root growth probably due to improved nutritional status (Alvarez-Clare & Mack 2015, Consalter et al 2021a.…”
Section: General Effect Of Fertilizationsupporting
confidence: 89%
“…In a 16-year-old forest, Albaugh et al (2004) found increases of 100% and 130 % in total aboveground and belowground biomass, respectively; this corroborates findings obtained in the present study. In addition to the direct effect of nutrients, the Ca/Al ratio of roots can also influence root growth in response to fertilizer and limestone use (Adam et al 2021). Thus, a more vigorous loblolly pine root system translates into greater water and nutrient acquisition efficiencies, which along with higher nutrient supply via fertilization and liming, contributes to greater aboveground growth (in relation to height and trunk diameter) that favors wood production.…”
Section: General Effect Of Fertilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Silvicultural management in forest plantations can increase tree growth in P. taeda plantations, especially in the long term, through the contribution of forest residues from previous harvest crops (Adam et al 2021). We hypothesized that the microbial activity in the soil of P. taeda plantations is correlated to some physical and chemical attributes resulting from the soil pedogenesis as well as from the soil and silvicultural management.…”
Section: Introductionmentioning
confidence: 99%